EBSG, a novel surface protein, is involved in the biology of Lipoteichoic acid in Enterococcus faecalis. - Kaltinger, Megan (Kansas State University, 2007)
Enterococcus faecalis is one of the most frequently encountered enterococcal isolates and accounts for about 80% of enterococcal infections. Treatment of enterococcal infections has become increasingly difficult as this organism has a high incidence of antibiotic resistance. Lipoteichoic acid (LTA) is an essential amphiphilic polymer on the surface of most Gram positive bacteria. While the molecule's exact role is not yet fully understood, a role in cell-cell contact during conjugation enabling the spread of extra chromosomal elements has been discussed. LTA also has implications in regulating autolysis, sequestering cations to the cell surface, adhesion, biofilm formation, antibiotic resistance, UV sensitivity, acid tolerance, and virulence. The gene ebsG was identified in a mutant of E. faecalis with major alterations in LTA structure and decreased ability to act as a recipient in conjugative mating. ebsG codes for a 119 kDa protein with only weak homology to other surface proteins of Gram positive bacteria. Transcriptional linkage analysis indicated ebsG and its downstream genes are organized in an operon. LTA analysis reveals a higher glycosyl content of the molecule in the mutant during stationary phase. Compared to wild type OG1RF, the mutant is more sensitive to nisin, shows higher autolysis activity during stationary phase, and is better able to serve as a recipient in plasmid transfer. Our data indicate ebsG and the members of the operon play a role in LTA structure and may act to degrade LTA.
Keywords: Enterococcus faecalis; lipoteichoic acid; EbsG; Biology, Microbiology (0410)